Rooibos - a good choice! - Karolina Bernacka; Katarzyna Bednarska; Iwona Urbanowicz; Izabela Fecka (Polish Pharmaceutical Society, 2021)
Aspalathus linearis (Burman f.) R. Dahlgren is a shrub of the Fabaceae family, growing endemically in southern Africa. Aspalathus linearis has transformed from a wild plant to a cultivated crop. Now it is commercially available as fermented (red) rooibos and the less common unfermented (green) rooibos. This article aimed to review the literature on the redbush with a focus on its health-promoting properties. Numerous laboratory investigations of extracts and infusions of A. linearis have shown that rooibos is a rich source of biologically active compounds, especially polyphenols. The active compounds present in redbush infusions and extracts include flavonoids, phenolic acids, and minute amounts of procyanidins, coumarins, lignans, phenylethanoids, and phenylpropanoids. The characteristic active compounds of rooibos are the C-glucosyl dihydrochalcone - aspalathin and notofagin. An important active compound found in the infusion is also PPAG (Z-2-(beta-D-glucopyranosyloxy)-3-phenylpropenoic acid), which significantly determines the sensory quality of the infusion and its hypoglycaemic properties. Rooibos is also a source of minerals. Studies in both experimental models and healthy volunteers have confirmed the multiple effects of the redbush. The antioxidant properties of A. linearis were especially well studied. The greater antioxidant activity has been reported for aspalathin-rich green rooibos. The consumption of redbush infusions has been reported to have beneficial effects on the parameters like total plasma antioxidant capacity, lipid peroxidation index, and blood glutathione levels. Rooibos has also been shown to alleviate the inflammatory process induced by lipopolysaccharides or that associated with colitis. This is underlined by reduced expression of pro-inflammatory factors, as well as antioxidant properties. Redbush may be used in supporting the treatment of glucose and lipid metabolism disorders, endocrine disorders, and metabolic syndrome. It has been proven to stimulate pancreatic cells to secrete insulin, regulate the expression of genes responsible for glucose metabolism, and affect the amount of glucose transporter protein type 4 (GLUT-4). Other health properties of rooibos may include antimutagenic and hepatoprotective properties and acceleration of skin healing. The bioavailability of redbush flavonoids and the interaction of rooibos ingredients with drugs were also investigated. Studying the mechanism of absorption of flavonoids contained in the redbush and their interactions with drugs will allow determining the appropriate dosage of the extracts. Precise recognition of the chemical composition and health-promoting properties of the redbush will enable its utilization as pharmacotherapy support.